2016
DOI: 10.1055/s-0036-1592420
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Performance after Brain Arteriovenous Malformations Treatment

Abstract: The treatment of brain arteriovenous malformations (AVMs) has been studied extensively. With the use of the Spetzler-Martin (S-M) grading system, patients can be informed appropriately about their possible surgical risks. This does not hold true for their neuropsychological sequelae, which have not been studied widely. We evaluated the neuropsychological outcome of our patients treated for brain AVMs. Of 113 patients treated for a brain AVM between 2001 and 2009, 66 patients were enrolled in the study. All pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…According to the results of our neuropsychological testing, patients with non-obliterated high-grade AVMs (S-M IV-V) scored worse than patients harboring AVMs S-M grade I to III. This nding indicates a possible con rmation of the steal phenomenon, which other authors suggested as the main reason for neuropsychological and neurologic improvement after AVM occlusion [3].…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…According to the results of our neuropsychological testing, patients with non-obliterated high-grade AVMs (S-M IV-V) scored worse than patients harboring AVMs S-M grade I to III. This nding indicates a possible con rmation of the steal phenomenon, which other authors suggested as the main reason for neuropsychological and neurologic improvement after AVM occlusion [3].…”
Section: Discussionsupporting
confidence: 62%
“…Although the nal results of the ARUBA study supported a conservative watch-and-wait strategy, these results were based on 98 actively treated patients, and of these 116 patients, only 18 patients underwent surgical excision alone or in combination with other treatment modalities. So, the ARUBA study was not powered to distinguish among different treatment modalities [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation